Age-Related Effects in the Neocortical Organization of Chimpanzees: Gray and White Matter Volume, Cortical Thickness, Gyrification - Autrey, Michelle M. (2014)
Among primates, humans exhibit the most profound degree of age-related brain volumetric decline in particular regions, such as the hippocampus and the frontal lobe. Recent studies have shown that our closest living relatives, the chimpanzees, experience little to no volumetric decline in gray and white matter over the adult lifespan. However, these previous studies were limited with a small sample of chimpanzees of the most advanced ages. In the present study, we sought to further test for potential age-related decline in cortical organization in chimpanzees by expanding the sample size of aged chimpanzees. We used the BrainVisa software to measure total brain volume, gray and white matter volumes, gray matter thickness, and gyrification index in a cross-sectional sample of 219 captive chimpanzees (8-53 years old), with 38 subjects being 40 or more years of age. Mean depth and cortical fold opening of 11 major sulci of the chimpanzee brains were also measured. We found that chimpanzees showed increased gyrification with age and a cubic relationship between age and white matter volume. For the association between age and sulci depth and width, the results were mostly non-significant with the exception of one negative correlation between age and the fronto-orbital sulcus. In short, results showed that chimpanzees exhibit few age-related changes in global cortical organization, sulci folding and sulci width. These findings support previous studies and the theory that the age-related changes in the human brain is due to an extended lifespan.